2016
DOI: 10.1039/c6cs00286b
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-bond promoted nucleophilic fluorination: concept, mechanism and applications in positron emission tomography

Abstract: Due to the tremendous interest in carbon-fluorine bond-forming reactions, research efforts in this area have been dedicated to the development of facile processes to synthesize small fluorine-containing organic molecules. Among others, PET (Positron Emission Tomography) is one of the most important applications of fluorine chemistry. Recognizing the specific requirements of PET processes, some groups have focused on fluorination reactions using alkali metal fluorides, particularly through SN2-type reactions. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
96
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(98 citation statements)
references
References 50 publications
2
96
0
Order By: Relevance
“…[11] Unsurprisingly,t od ate, no transition-metal-catalyzed fluorinations in alcoholicm edia have been reported. [11] Unsurprisingly,t od ate, no transition-metal-catalyzed fluorinations in alcoholicm edia have been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[11] Unsurprisingly,t od ate, no transition-metal-catalyzed fluorinations in alcoholicm edia have been reported. [11] Unsurprisingly,t od ate, no transition-metal-catalyzed fluorinations in alcoholicm edia have been reported.…”
mentioning
confidence: 99%
“…[10] Figure 2. The introduction of O-a nd N-containing substitu- 11)f rom the corresponding unprotected precursors, albeit in lower RCCs of up to 10 and 21 %, respectively. To demonstrate the versatility of the procedure, we radiofluorinated as eries of (hetero)arylboronic substrates ( Figure 5).…”
mentioning
confidence: 99%
“…[2] Such changes could, to a great extent, benefit pharmaceutical, [3] agrochemical, [4] material, [5] and radiotracer (positron emission tomography) sciences. [6] In the pharmaceutical industry, the amount of currently administered fluorine-containing drugs have increased to around 30 % of marketed drugs.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy to mention that part of the alkali metal fluoride mediated nucleophilic fluorination involved in this Minireview has been well-reviewed by Song and co-workers. [6c] …”
Section: Introductionmentioning
confidence: 99%
“…[10d] Another problem with MF salts is their poor solubility in most organic solvents.Since fluoride itself is agood hydrogenbond acceptor,aH-bond network could complex with MF and make it highly soluble.I ndeed, alkali fluorides,s uch as KF, have good solubility in HFIP at room temperature.A lso,i t has been reported that F À is ab etter nucleophile than other halides (Br À /I À )inhydrogen-bonding donor solvents,such as tBuOH, owing to their positive effect on the "effective fluoride nucleophilicity". [11] Because HFIP is as tronger Hbond donor than those alcohols,w ee xpected it to have an even stronger effect in the modulation of the nucleophilicity of fluoride.F inally,aH-bond network generated from HFIP could also act as ap roton source in hydrofluorination (Scheme 1c), as shown by Doyle and co-workers in their copper-catalyzed HÀFi nsertion into a-diazocarbonyl compounds with HFIP as the proton source. [12] We are now glad to report the first protocol for 18 Faddition to an alkyne through anucleophilic (radio)fluoroclick reaction, enabled by ahydrogen-bonding cluster and using readily available KF( 18 F) (Scheme 1d).…”
mentioning
confidence: 99%